Quadrinhos digitais: uma análise das novas possibilidades - Bernardi, Bianca Paneto (2014)
The comic is one of the oldest forms of recorded mankind history and have been evolving and undergoing significant changes over time. Technological advances have significantly changed the concepts and ways of viewing the comics and are these changes and possibilities of representation that will be analyzed and described in this dissertation. Starting with a historical analysis and proceeding to an aesthetic analysis, this research highlighted the different features acquired by this form of production of communication language. As society changes its forms of expression and language will be changing , the subjects worked in the comics will also change, as well as narrative developed , the aesthetic representations and different materials to be used . Based on the work and research by Moacy Cirne , Scott McCloud and Edgar Franco was possible to view the panorama of comics to this day . By working with the concepts of ciberculture, by Pierre Lévy and convergence culture, by Jenkins it was possible a deep study inside the digital comics.The advent of the internet and the development of new software and hardware made possible the integration and exploitation of new syntactic and semantic elements in this form of production. The hypermedia systems, interactivity, collective production, tridimensionality, sounds and animations changed the ways of producing and interpreting the comics. It was observed that the Opportunities established by mobile systems that are more recent, and also bring new possibilities for developing narratives and representations, such as augmented reality and the use of motion sensors in phones and tablets. This study analyzed the most interesting and alternatives that have emerged to date, because we know that language is alive and that new proposal can and should emerge over the years and the development of new technologies